Analysis of Thesis in Turkey between the years 2008-2020 on Mathematics Literacy - Ayşe Arzu Arı; Barış Demir (Sakarya University Journal of Education)
In recent years, the concept of mathematical literacy has become the main subject of studies on mathematics education. Although there are many graduate theses on mathematics literacy in the current situation, no detailed analysis of them has been found. The purpose of this work, what needs the quantity and quality of the arguments made on mathematics literacy in Turkey meets the criteria, what kind of research is needed to reveal whether the analysis using meta-synthesis method. In the research, the postgraduate theses that were studied on mathematics literacy between 2008 and 2019 and determined by purposeful sampling method were analyzed. The graduate theses examined in the research were obtained as a result of the search made in the database of the Higher Education Council (YÖK) National Thesis Scanning Center. This study is limited to 66 (51 master's and 15 doctoral) postgraduate theses that have been completed on literacy in the field of mathematics education until 2019. The data obtained in the study were analyzed in terms of the university, years and type of theses on mathematics literacy, sample characteristics, targeted purposes, methods used and data collection tools. The obtained data are shown with the help of graphics and tables with frequency. It has been observed that the number of master's and doctoral theses prepared since 2008 has increased, the number of doctoral theses is one-third of the number of master's theses and most of the theses are exited from Uludağ University. In the study, it was determined that most of the theses were carried out to examine mathematical literacy in the context of PISA. It was observed that quantitative screening method was used as the research method most, and questionnaire / scale and tests were used as data collection tools, and studies conducted with students and secondary school level were the majority.